Building Character Through Self-Identification in Indonesian Overseas School Students in Saudi Arabia - Z., Anis Fuadah; Sibawaihi, Sibawaihi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Building character through self-identification in students of Indonesian Overseas Schools in Saudi Arabia is an important study to discuss. Students' character does not grow only by accepting theories and concepts in classroom learning, but it requires habits in their daily lives so that it becomes a habitual attitude. This study aims to capture the attitude of respect for students at SILN Saudi Arabia towards themselves, others, the environment, and the multicultural relationships they experience. This study uses a qualitative descriptive approach with the concept's foundation of moral education by Syekh Al-Zarnuji in the book Ta’lim Muta’alim and Will Kymlicka's multicultural theory as the basis for its study. The main finding in this study is the uniqueness of students' characters, shown in positive attitudes in daily life. This good attitude positively affects students' personal lives and has implications for their survival when interacting with others. The recommendation in this study is the need to build synergy between schools, guardians of students and the community, so that the development of good character in students can be maintained when they are at home, at school, or while doing activities in the community, as well as in their lives in the future.